The influence of oculomotor tasks on postural control in dyslexic children - Bucci, Maria Pia; Mélithe, Damien; Ajrezo, Layla; Bui-Quoc, Emmanuel; Gérard, Christophe-Loic (Frontiers in Human Neuroscience, 2014)
Dual task is known to affect postural stability in children. We explored the effect of visual tasks on postural control in thirty dyslexic children. A selected group of thirty chronological age-matched non-dyslexic children (mean age: 9.92 ± 0.35 years) and a group of thirty reading age-matched non-dyslexic children (mean reading age: 7.90 ± 0.25 years) were chosen for comparison. All children underwent ophthalmologic and optometric evaluation. Eye movements were recorded by a video-oculography system (EyeBrain® T2) and postural sway was recorded simultaneously by a force platform (TechnoConept®). All children performed fixations, pursuits, pro- and anti-saccades tasks. Dyslexic children showed significantly poor near fusional vergence ranges (convergence and divergence) with respect to the non-dyslexic children groups. During the postural task, quality of fixation and anti-saccade performance in dyslexic children were significantly worse compared to the two non-dyslexic children groups. In contrast, the number of catch-up saccades during pursuits and the latency of pro- and anti-saccades were similar in the three groups of children examined. Concerning postural quality, dyslexic children were more unstable than chronological age-matched non-dyslexic children group. For all three groups of children tested we also observed that executing saccades (pro- and anti-saccades) reduced postural values significantly in comparison with fixation and pursuit tasks. The impairment in convergence and divergence fusional capabilities could be due to an immaturity in cortical structures controlling the vergence system. The poor oculomotor performance reported in dyslexic children suggested a deficit in allocating visual attention and their postural instability observed is in line with the cerebellar impairment previously reported in dyslexic children. Finally, pro- or anti-saccades reduce postural values compared to fixation and pursuit tasks in all groups of children tested, suggesting a different influence of visual tasks on postural control according to their attentional demand.